Use of heritage to learn history in preschool education. Educational experience: This class is a museum! - Escribano-Miralles, Ainoa (Pulso. Revista de educación, 2015)
Out of all the topics that are studied in the social sciences in preschool education, the passing of time and cultural heritage are given the least amount of attention. One of the principal causes postulated by Piaget is that a preschool child is unable to understand the importance of history and historical art. Certain authors that specialise in the didactics of social sciences have demonstrated, through a research study and practical proposals, that it is possible to study history in preschool education (Cooper, 2002; Miralles and Molina, 2011). However, the objective is to study in depth the teaching of history in preschool by designing, applying and evaluating a didactic proposal for the teaching of history, by studying cultural heritage and using the entire classroom. This proposal was conducted in a class of 21 five-year-old students in a school in Murcia, Spain. It demonstrated that it is possible to study history through cultural heritage by means of a project that involves the whole classroom and the museum.